Assessing the contrast sensitivity function in myopic parafovea: A quick contrast sensitivity functions study - Xu, Zixuan; Zhuang, Yijing; Chen, Zhipeng; Hou, Fang; Chan, Lily Y. L.; Feng, Lei; Ye, Qingqing; He, Yunsi; Zhou, Yusong; Jia, Yu; Yuan, Junpeng; Lu, Zhong-Lin; et al. (Frontiers in Neuroscience, 2022)
Purpose: Compare peripheral contrast sensitivity functions (CSF) between myopes and emmetropes to reveal potential myogenic risks during emmetropization. Methods: This observational, cross-sectional, non-consecutive case study included data from 19 myopes(23.42±4.03 years old) and 12 emmetropes(22.93±2.91 years old) who underwent central and peripheral quick CSF (qCSF) measurements. Summary CSF metrics including the cut-off spatial frequency (cut-off SF), area under log CSF(AULCSF), low-, intermediate-, and high-spatial-frequency AULCSFs (l-, i-, and h-SF AULCSFs), and log CS at 19 SFs in the fovea and 15 peripheral locations (superior, inferior, temporal, and nasal quadrants at 6º, 12º, 18º, and 24º eccentricities, excluding the physiological scotoma at 18º) were analyzed with 3-way and 4-way between-subjects analysis of variance(ANOVA) (α=0.05). Results: 3-way ANOVA showed that myopes had significantly increased AULCSF at 6º (mean difference, 0.08; 95% CI, 0.02-0.13; P=0.007) and 12º (mean difference, 0.09; 95% CI, 0.03-0.14; P=0.003). Log CS at all 19 SFs were higher in the myopia group compared to the normal group (mean differencesuperior, 0.02; 95% CI, 0.01-0.20; P=0.02 and mean differenceinferior, 0.11; 95% CI, 0.02-0.21; P=0.01) at 12º. The h-SF AULCSF at 6º (mean differenceinferior, 1.27; 95% CI, 0.32-2.22; P=0.009) and i-SF AULCSF at 12° (mean differencesuperior, 5.31; 95% CI, 4.35-6.27; P<0.001; mean differenceinferior, 1.14; 95% CI, 0.19-2.10; P=0.02) were higher in myopia versus normal group. Conclusion: We found myopia increased contrast sensitivity in superior and inferior visual field locations at 6º parafoveal and 12º perifoveal regions of the retina. The observation of increased contrast sensitivities within the macula visual field in myopia might provide important insights for myopia control during emmetropization.